Challenges to sustainable development in Mississippi. Issue 5 (19th October 2016) - Liew, Hui
Abstract: To date, various constituents have attempted to improve the economic opportunities in Mississippi through entrepreneurship, small business development, and job creation/workforce development and wastewater treatment. However, none have explicitly focused on avenues toward sustainable development in terms of poverty eradication and achieving equitable resource allocation. This study seeks to empirically derive the challenges to sustainable development in Mississippi by forming clusters of counties with similar socioeconomic, demographic, health, and environmental characteristics. Maps created through ArcGIS software are used in conjunction with the cluster analysis to visualize the data. Cluster analysis yielded three distinct clusters. Priority should be given to counties that are predominantly black, rural, and characterized by high unemployment and high poverty. Special attention should also be implemented in counties characterized by a high unmet need for health services and a low density of medical professionals.